Imagining and critical reflection in autobiography: An odd couple in adult transformative learning. - Alex Nelson (Adult Education Research Conference, 1997)
Adult education approaches to transformative learning generally emphasize the interpretive role of critical reflection and critical thinking. This explanatory understanding of transformative learning as autobiography claims that the learner composes their life, by using imagination and critical reflection to interpret their life story within the social context.